2020
DOI: 10.3390/polym12071487
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Black Phosphorus/Boron Nitride Nanosheets on Enhancing the Flame-Retardant Properties of Waterborne Polyurethane and Its Flame-Retardant Mechanism

Abstract: We applied black phosphorene (BP) and hexagonal boron nitride (BN) nanosheets as flame retardants to waterborne polyurethane to fabricate a novel black phosphorus/boron nitride/waterborne polyurethane composite material. The results demonstrated that the limiting oxygen index of the flame-retarded waterborne polyurethane composite increased from 21.7% for pure waterborne polyurethane to 33.8%. The peak heat release rate and total heat release of the waterborne polyurethane composite were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Composites also showed an increment of the temperature corresponding to the maximum degradation rate ( Table 2 ). These encouraging results about the improved thermal stability of the PS/PMMA blend agree with previous data indicating that fl-bP inhibits mass transfer and provides thermal insulation to shield the underlying polymer from the heat source [ 26 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Similar results have also been reported for other types of ultrathin 2D nanomaterials dispersed both in thermoplastic and thermosetting polymers [ 62 , 63 , 64 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Composites also showed an increment of the temperature corresponding to the maximum degradation rate ( Table 2 ). These encouraging results about the improved thermal stability of the PS/PMMA blend agree with previous data indicating that fl-bP inhibits mass transfer and provides thermal insulation to shield the underlying polymer from the heat source [ 26 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Similar results have also been reported for other types of ultrathin 2D nanomaterials dispersed both in thermoplastic and thermosetting polymers [ 62 , 63 , 64 ].…”
Section: Resultssupporting
confidence: 90%
“…This method improves the compatibility between bP and waterborne polyurethane matrix by improving the mechanical properties and flame retardancy. Furthermore, a very efficient flame retardant for this type of composite was obtained by combining bP and boron nitride [ 31 ]. Recently, it has also been shown that bP can improve both the mechanical properties and flame retardancy of epoxy resins [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used flame retardants are organic and inorganic phosphorus compounds. This type of flame retardant's wide range of applications is evidenced by the lack of release of toxic combustion products, reduced smoke emission, and increased flame retardancy [86]. The use of phosphorus flame retardants reduces the flammability of the polymer.…”
Section: Phosphorus-based Flame Retardantsmentioning
confidence: 99%
“…Based on the high thermal stability of boron nitride and its excellent chemical stability and high temperature oxidation resistance, boron nitride-based composite materials are also used as ideal flame-retardant materials. Yin et al [208] applied black phosphorene (BP) and h-BN nanosheets as flame retardant fillers in waterborne polyurethane to obtain a new type of waterborne polyurethane composite material. The results showed that the limiting oxygen index of the flameretardant waterborne polyurethane composite material increased from 21.7% of pure waterborne polyurethane to 33.8%.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%